Ginsenoside Rb1 Improves Cognitive Impairment Induced by Insulin Resistance through Cdk5/p35-NMDAR-IDE Pathway. (20th May 2020) - Yang, Ranyao; Jiang, Xue; He, Xiqian; Liang, Donglou; Sun, Shusen; Zhou, Guangyan
Abstract : The relationship between diabetes mellitus (DM) and Alzheimer's disease (AD) has attracted wide attention. Studies have reported that ginsenoside Rb1 can improve human cognitive ability and glucose tolerance during the development of diabetes. The mechanism behind the improvement in cognitive ability and glucose tolerance still remains unclear. In this study, streptozotocin- (STZ-) injected mice were used as models to explore the mechanisms behind the cognitive improvement of ginsenoside Rb1. According to the results of behavioral tests, ginsenoside Rb1 improved memory and cognitive ability of STZ-lesioned mice. In addition to that, ginsenoside Rb1 also relieved glucose intolerance induced by STZ injection by enhancing insulin sensitivity. These beneficial effects of ginsenoside Rb1 is most likely mediated by upregulating the expression of NMDAR1 and IDE in the hippocampus through inhibiting the activity of Cdk5/p35. This work will be of great importance in illustrating the mechanisms of ginsenoside Rb1 for improving cognitive ability, as well as revealing the relationship between diabetes and AD.